Human Resource Management in Efforts to Improve the Performance of Village-Owned Enterprises - Vano Elbar Dharma; Arumi Nasha (International Journal of Humanities and Social Sciences Reviews, 2024)
Human Resource Management is a critical aspect in efforts to improve the performance of Village-Owned Enterprises. The research results show that the implementation of effective HR management can make a significant contribution to improving the performance of BUMDes. Factors such as appropriate recruitment, employee training, motivation, and skills development are key to optimizing human potential in BUMDes. In addition, this research highlights the importance of implementing policies that support employee welfare, such as incentive programs and supporting facilities. With well-planned HR management, BUMDes can increase their productivity, innovation, and competitiveness in local and regional economic markets.